2004
DOI: 10.15807/jorsj.47.304
|View full text |Cite
|
Sign up to set email alerts
|

STABILITY OF A SIMPLE RE-ENTRANT LINE WITH INFINITE SUPPLY OF WORK : THE CASE OF EXPONENTIAL PROCESSING TIMES(<Special Issue>Network Design, Control and Optimization)

Abstract: We co"sider a two machine 3 step re-entrant line, with an infinite supply of work.We assume that processing times are exponentially distributed. We show that this system is stable under LBFS priority policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…in [3] and [6]. Jackson networks with an infinite supply of work are a special case of multiclass queueing networks with virtual infinite buffers, introduced in [2], [8], [9], and [10].Recall that all service and interarrival times in a Jackson network are independent and exponentially distributed. Also, assume that the routing matrix P has spectral radius less than 1,…”
mentioning
confidence: 99%
“…in [3] and [6]. Jackson networks with an infinite supply of work are a special case of multiclass queueing networks with virtual infinite buffers, introduced in [2], [8], [9], and [10].Recall that all service and interarrival times in a Jackson network are independent and exponentially distributed. Also, assume that the routing matrix P has spectral radius less than 1,…”
mentioning
confidence: 99%
“…It is straightforward to verify that (20) agrees with the QP in (14)- (18). Formulation (20) is in the form that is required by most commercial QP solvers.…”
Section: Detailed Description Of the Qpmentioning
confidence: 95%
“…In [1] (see also [20]) the authors have shown that a continuous-time reentrant line is stable when using the Last Buffer First Serve (LBFS) control that prioritizes step 3 over step 1, and a non-idling policy in server 2. This policy ensures that server 1 is maximally utilized.…”
Section: Example 2: Simple Reentrant Linementioning
confidence: 99%
See 1 more Smart Citation
“…Infinite GJN is an extension of Jackson network with an infinite supply of work in [13], and is a special case of multiclass queueing networks with virtual infinite buffers, which were introduced in [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%